Living together separately : Arabs and Jews in contemporary Jerusalem - Romann, Michael; Weingrod, Alex (Princeton studies on the Near East., 1991)
Focusing on the conduct of everyday life, rather than ideology. provides a look at the complex networks of practical relations developed by Jews and Arabs in over two decades of Israel control of the city (cont.).